The long Utopia - Pratchett, Terry; Baxter, Stephen (Pratchett, Terry. Long Earth series., 2015)
Lobsang's pursuit of a human life, Joshua's search for his father and the adaptation efforts of "the Next" post-humans are challenged by a voracious alien race that would conquer and colonize the Long Earth.